Diagnostic and Treatment Challenges of Paroxysmal Nocturnal Hemoglobinuria in Uganda - Boniface Amanee Elias Lumori; Daniel Muyanja (Case Reports in Hematology)
Introduction. Paroxysmal nocturnal hemoglobinuria (PNH) is a very rare disorder of the hematopoietic stem cells which is often underdiagnosed. Its incidence is about 5 cases per million inhabitants in a year, and currently, there are only 1610 patients in the International PNH Registry. In this report, we describe a case of PNH in southwestern Uganda. Case Presentation. A 34-year-old man, subsistence farmer, with a history of multiple prior presentations with anemia, jaundice, and dark-colored urine requiring blood transfusions presented to us again in July 2018 with a week’s history of palpitations, dizziness, and dark-colored urine. Investigations done suggested a direct antiglobulin test- (DAT-) negative hemolytic anemia, and subsequently, flow cytometry showed a large clone of PNH. He received many blood transfusions and hematinics on several occasions during the course of his admissions. Conclusions. Our report showed diagnostic and treatment challenges of PNH in health resource-limited setting.